2014
DOI: 10.1007/s10265-014-0658-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tomato SlTIP2;2 enhances the tolerance to salt stress in the transgenic Arabidopsis and interacts with target proteins

Abstract: Three independent transgenic Arabidopsis lines expressing SlTIP2;2 from Solanum lycopersicum L. cv. Lichun under the control of its endogenous promoter were used to analyze the expression of SlTIP2;2 and the salt stress tolerance under NaCl concentration gradient treatment. The expression patterns of SlTIP2;2 were shown to be tissue-specific and NaCl dose-dependent under salt stress. SlTIP2;2-transformed Arabidopsis plants exhibited enhanced salt stress tolerance, and the physiological parameters suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…The changes in osmotic potential are generally related to the influx or efflux of Na and K ions in the root tips. The overexpression of the SlTIP2;2 gene in the transgenic Arabidopsis significantly decreases the K efflux and Na influx in the root tips under salt stress [22]. AtLOS5 overexpression in transgenic maize enhances the net Na efflux in the roots but decreases the net K efflux [23].…”
Section: Discussionmentioning
confidence: 99%
“…The changes in osmotic potential are generally related to the influx or efflux of Na and K ions in the root tips. The overexpression of the SlTIP2;2 gene in the transgenic Arabidopsis significantly decreases the K efflux and Na influx in the root tips under salt stress [22]. AtLOS5 overexpression in transgenic maize enhances the net Na efflux in the roots but decreases the net K efflux [23].…”
Section: Discussionmentioning
confidence: 99%
“…Tonoplast intrinsic proteins, as a major and plant-specific subfamily of AQPs, can regulate water exchange between the cytoplasm and vacuole and control cell water homeostasis involved in cellular storage, osmotic adjustment and turgor control, cell signaling and digestion, and abiotic stress tolerance (Peng et al, 2007; Wang et al, 2011; Xin et al, 2014; Song et al, 2016). Therefore, plants or crops may be conferred with increased tolerance toward different abiotic stresses through a suitable TIP -transgenic approach (Srivastava et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ectopic overexpression of TsTIP1;2 from the halophyte Thellungiella salsuginea in Arabidopsis notably increased tolerance for drought, salt, and oxidative stresses (Wang et al, 2014). Transgenic Arabidopsis plants expressing SlTIP2;2 from Solanum lycopersicum exhibited enhanced salt stress tolerance by regulating ion (including Na + and K + ) homeostasis and antioxidant enzyme activities under salt treatment (Xin et al, 2014). A high water channel activity was displayed by PgTIP1- heterologous expression in Xenopus laevis oocytes and in yeast, and a significant role in growth and development under favorable conditions and enhanced salt and drought tolerance, together with upregulated expression of the stress-related genes, was demonstrated in PgTIP1- transgenic Arabidopsis plants (Lin et al, 2007; Peng et al, 2007; Li and Cai, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Xin et al (2014) showed that transgenic Arabidopsis plants expressing SlTIP2;2 possessed enhanced tolerance of salinity. In addition, yeast two-hybrid and BiFC analysis in protoplasts determined the physical binding between SlTIP2;2 from tomato ( Solanum lycopersicum ) and the UDP-galactose transporter (Xin et al, 2014). …”
Section: Protein–protein Interactionsmentioning
confidence: 99%
“…The great number of AQPs in plants, the different substrates that they transport (Li et al, 2014) and the diverse forms of molecular regulation (Yaneff et al, 2015) make the study of the physiological role of AQPs a great challenge. To this complicated landscape, we have to add the recent discovery of AQP-protein and AQP-AQP interaction, which affect the regulation of aquaporin functionality (Fetter et al, 2004; Xin et al, 2014). …”
Section: Introductionmentioning
confidence: 99%